(untitled) (Atlas Journal of Biology, 2017)
The International American Moroccan Agricultural Sciences Conference (AMAS Conference; www.amas-conference.org) is an international conference organized by the High Council of Moroccan American Scholars and Academics (HC-MASA; www.hc-masa.org) in collaboration with various universities and research institutes in Morocco. The first edition (AMAS Conference I) was organized on March 18-19, 2013 in Rabat, Morocco; AMAS Conference II was organized on October 18-20, 2014 in Marrakech, Morocco; and AMAS III was organized on December 13-16, 2016 in Ouarzazate, Morocco. The current proceedings summarizes abstracts from 62 oral presentations and 100 posters that were presented during AMAS Conference III.